Fungal Appendicitis in Immunocompromised Children. Indications and Contraindications for Laparoscopic Appendectomy: A Report on 2 Successful Cases. Issue 7 (October 2016) - Carlini, Veronica; Calcaterra, Valeria; Decembrino, Nunzia; Rubert, Laura; Pasqua, Noemi; Novario, Mattia; Lucioni, Marco; Brunero, Marco; Pelizzo, Gloria
Abstract : In leukemic patients, appendectomy must be approached with caution because of the increased risk of complications. Fungal appendicitis is rare and only a few cases have been described in the literature, particularly in immunocompromised individuals in whom this infection can be fatal. We present 2 pediatric patients with acute myeloid leukemia, who developed appendicitis during the postchemotherapy neutropenic phase, while receiving antifungal prophylaxis. Fever was the first sign of infection. Laparoscopic appendectomy was performed without postoperative complications. The histologic examination and the culture analysis showed the presence of fungal elements; systemic fungal infection was also excluded. The risk is increased in immunocompromised children with fungal appendicitis and the signs of peritoneal irritation are not always obvious. The histopathologic demonstration of fungal elements and tissue reaction is mandatory for a definitive diagnosis. Laparoscopic appendectomy should be considered as the gold standard procedure to avoid fungal dissemination. Moreover, laparoscopic surgery and its inherent mini-invasive surgical advantages may improve the overall survival without incurring significant complications.